2014
DOI: 10.1182/blood-2014-05-577361
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of somatic MAP2K1 mutations in BRAF V600E–negative Langerhans cell histiocytosis

Abstract: • Targeted

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
220
1
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 335 publications
(240 citation statements)
references
References 20 publications
11
220
1
8
Order By: Relevance
“…Similar small in-frame deletions within exon 2 of MAP2K1 were recently reported in most Langerhans cell histiocytosis cases lacking BRAF p.V600E mutation, where it functions as an alternate mechanism of MAP kinase pathway activation. 21,22 Given the unresectable nature of this patient's tumor and medically refractory seizures, targeted therapy with the MEK inhibitor trametinib is being considered.…”
Section: Neurooncologymentioning
confidence: 99%
“…Similar small in-frame deletions within exon 2 of MAP2K1 were recently reported in most Langerhans cell histiocytosis cases lacking BRAF p.V600E mutation, where it functions as an alternate mechanism of MAP kinase pathway activation. 21,22 Given the unresectable nature of this patient's tumor and medically refractory seizures, targeted therapy with the MEK inhibitor trametinib is being considered.…”
Section: Neurooncologymentioning
confidence: 99%
“…The proliferating Langerhans cells have abundant,oftenvacuolatedcytoplasmandvesicularnucleicontaininglineargroovesorfolds.Thepresence ofBirbeckgranulesinthecytoplasmischaracteristic.BRAFV600Emutationswerefoundin38%to 57% of LCH cases. MAP2K1 mutation is another knownmutation [9]. [7,8].…”
Section: Discussionmentioning
confidence: 99%
“…Targeted sequencing studies identified MAP2K1 mutations in 15%-50% of cases with wild-type BRAF (Figure 2). 20,21 Another WES study of 3 LCH cases revealed 1 lesion with BRAF-V600E, 1 with a complex somatic activating mutation in ARAF, and 1 without MAPK gene mutations identified. As in our series, Nelson et al also described a very low overall rate of somatic mutations.…”
Section: Molecular Landscape Of Lch: Mapk Activationmentioning
confidence: 99%